Methanol Extract of Citrullus Lanatus Rind and Silymarin Modulates Liver Function, Haematological Profile, and Liver Antioxidant Status in Thioacetamide-Treated Male Wistar Rats - Ebhohon, Shirley O.; Ojowu, J. O.; Adarki, W. P.; Edward, U. I. (Journal of Science Research and Reviews, 2024)
Thioacetamide (TAA) is known to induce hepatotoxicity and oxidative stress, disrupting liver function and body weight in experimental animals. This study evaluated the hepatoprotective and antioxidant potential of methanolic Citrullus lanatus (watermelon) rind extract at 250 mg/kg and 500 mg/kg, as well as silymarin (50 mg/kg), in male Wistar rats treated with TAA (300 mg/kg). Body weight, liver weight, liver function markers, hematological parameters, and antioxidant enzyme activities were assessed. Results showed that TAA significantly decreased body weight and increased liver weight (p < 0.05), indicating hepatotoxicity. However, both doses of C. lanatus and silymarin significantly mitigated these effects, with the 500 mg/kg dose showing the strongest protective action. Alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), total bilirubin, albumin, total protein, and oxidative stress markers (Malondialdehyde, Reduced Glutathione, Superoxide Dismutase, Catalase, Glutathione Peroxidase) were significantly altered in the TAA group but were restored to near-normal levels in rats treated with C. lanatus and silymarin. Additionally, hematological indices (Red Blood Cells, Haemoglobin, Packed Cell Volume, Mean Corpuscular Volume, Mean Corpuscular Haemoglobin, Mean Corpuscular Haemoglobin Concentration, White Blood Cells, and Platelets) were significantly improved by the treatments, with the 500 mg/kg extract and silymarin exhibiting comparable efficacy. These findings suggest that C. lanatus rind extract possesses potent antioxidant and hepatoprotective properties, making it a promising therapeutic agent for managing TAA-induced liver damage. Further studies are recommended to explore its long-term safety and clinical applications.